Rapid Green Synthesis of Silver Nanoparticles by Reishi and Their Antibacterial Activity and Mechanisms - Ewunkem, Akamu J.; Priester, T’nasia; Williams, Desia; Ariyon, Bailey; Tshimanga, Ilunga; Justice, Brittany; Singh, Dinesh K. (Journal of biomaterials and nanobiotechnology, 2024)
Nanotechnology is a rapidly growing field in biomedical engineering with references to efficiency, safety, and cost-effective approaches. Herein, the objective of this study was to examine an innovative approach to rapidly synthesis silver nanoparticles from an aqueous extract of medicinal mushroom Ganoderma lucidum (also known as reishi). The structural and dimensional dispersion of the biosynthesized silver nanoparticles from reishi was confirmed by UV-Vis spectrophotometer (UV-Vis) and Scanning Electron Microscopy (SEM) analysis. Additionally, the biosynthesized silver nanoparticles from resihi were used to explore their potential antimicrobial activity against Staphylococcus aureus and Micrococcus luteus and Escherichia coli and Klebsiella pneumoniae . The results from this study revealed that the silver nanoparticles mediated by reishi adopted a spherical shape morphology with sizes, less than 100 nm and revealed strong absorption plasmon band at 440 nm. Furthermore, the biosynthesized silver nanoparticles from reishi exhibited antibacterial activity against the tested S. aureus and M. luteus and E. coli and K. pneumoniae by altering their morphology which signifies their biomedical potential.